2018
DOI: 10.1111/eea.12638
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of female melon fly, Zeugodacus cucurbitae, with cue‐lure and fipronil bait stations through horizontal insecticide transfer

Abstract: Melon fly, Zeugodacus cucurbitae (Coquillett) (Diptera: Tephritidae), is an important quarantine tephritid fruit fly with resident populations established in Hawai'i, USA. In the male‐annihilation approach, male flies are targeted using dispensers with cue‐lure (C‐L) and insecticides, typically organophosphates. The efficacy of the male annihilation approach is thought to be limited to individual male flies, contacting the lure and the pesticide, after which they die. Alternative classes of insecticides, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
7
1
Order By: Relevance
“…This was more pronounced following oral ingestion, where the full effects were not observed until 72 h post‐exposure. In comparison, Spafford et al, 2018 reported that male mortality approached 100% only 3 h following exposure, with female receivers following at 100% mortality by 6 h. In comparison, GS‐Hv1a‐dosed females directly treated in our study, only reached similar levels of mortality after nearly 72 h. After 24 h, mortality was only 25%, even at a concentration of 3.86%, the highest rate we tested. Additional research may be needed to determine an optimal dose of GS‐Hv1a to target females during this window while maintaining palatability.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…This was more pronounced following oral ingestion, where the full effects were not observed until 72 h post‐exposure. In comparison, Spafford et al, 2018 reported that male mortality approached 100% only 3 h following exposure, with female receivers following at 100% mortality by 6 h. In comparison, GS‐Hv1a‐dosed females directly treated in our study, only reached similar levels of mortality after nearly 72 h. After 24 h, mortality was only 25%, even at a concentration of 3.86%, the highest rate we tested. Additional research may be needed to determine an optimal dose of GS‐Hv1a to target females during this window while maintaining palatability.…”
Section: Discussioncontrasting
confidence: 58%
“…Both lure and toxicant are impregnated in a small rectangular piece of fibreboard. Because fipronil is slow acting, the males are able to then transfer the insecticide to females they later contact (Spafford et al, 2018). This is advantageous, as female management is otherwise limited to on‐crop applications of less attractive protein‐based lures and broad‐spectrum insecticides, which require greater volume of product and can lead to non‐target effects on beneficial species (Vargas et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Male annihilation technique consists of the deployment of high-density trapping stations with male-specific lures combined with an insecticide. The use of cuelure (the pheromone 4-(p-acetoxyphenyl)-2-butanone, which is highly attractive to male Z. cucurbitae ) laced with fipronil, has been used successfully against Z. cucurbitae and fruit fly species in genera Bactrocera (Spafford et al 2018). Among the biopesticides used in sub-Saharan Africa, Metarhizium anisopliae (Mechnikoff) Sorokin (Hypocreales: Clavicipitaceae) isolate ICIPE 69 (Real IPM, Thika, Kenya) is widely used as a fungal biopesticide (Akutse et al 2020) and has been found to be highly potent against Z. cucurbitae (Onsongo et al 2019).…”
Section: Introductionmentioning
confidence: 99%